Strong Convergence Results for Continuous Hemicontractive Mappings in Hilbert Spaces - Akuchu, B. G.; Okoro, A. O.; Nwigbo, K. T.; Chukwuyere, P. C. (Communications in Mathematics and Applications, 2020)
We use an iteration process due to Rafiq (A. Rafiq, On Mann iteration in Hilbert spaces, Nonlinear Analysis 66 (2007), 2230 – 2236) to approximate fixed points of continuous hemicontractive mappings in Hilbert spaces. We drop the compactness condition on the domain of the operator, imposed in [1] and [26]. Our results extend several well known results in the literature and complement the results in [1] and [26].